Measuring The Success of E-Learning In Universities Using The Technology Acceptance Model - Yudhana, Anton; Riadi, Imam; Abe, Tuska (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2022)
This study aims to determine the factors of acceptance of e-learning technology in students who use the technology acceptance model, namely perceived usefulness (PU), perceived ease of use (PEOU), an attitude of acceptance of use (ATU), and acceptance (IT) of the e-learning acceptance system. The population in this study were students of state Islamic religious institutes who had participated in the e-learning system. The respondents of this study were students of the Ambon State Islamic Institute of Religion, which collected 30 respondents. The method used in this study uses the technology acceptance model method in the process of data processing using quantitative analysis techniques in the process of analyzing data from research results. The analysis results show that the acceptance of e-learning technology by students of the Islamic Institute of Religion is very well received by users of the Ambon State Islamic Institute of Religion students. The study's results showed that the variable utilization percentage of 76.66% was stated to agree strongly. In comparison, the percentage of 61.66% agreed. Attitudes towards users 70.66% agreed. The study's results show that students in the learning process can accept using e-learning systems.